Development and validation of nomogram including high altitude as a risk factor for COPD: A cross-sectional study based on Gansu population - Lin, Ao; Mao, Chun; Rao, Boqi; Zhao, Hongjun; Wang, Yunchao; Yang, Guokang; Lei, Haisheng; Xie, Chenli; Huang, Dongsheng; Deng, Yibin; Zhang, Xuhui; Wang, Xinhua; et al. (Frontiers in Public Health, 2023)
Background Chronic Obstructive Pulmonary Disease (COPD) is a common and harmful disease that requires an effective tool to early screen high-risk individuals. Gansu has unique environments and customs, leading to the different prevalence and etiology of COPD from other regions. The association between altitude and COPD once attracted epidemiologists' attention. However, the prevalence in Gansu and the role of altitude are still unclarified. Methods In Gansu, a multistage stratified cluster sampling procedure was utilized to select a representative sample aged 40 years or older. The questionnaire and spirometry examination were implemented to collect participants' information. The diagnosis and assessment of COPD were identified by the Global Initiative for Chronic Obstructive Lung Disease (GOLD) criterion, while post-bronchodilator FEV1/FVC < LLN was for sensitivity analysis. Furthermore, the effect of high altitude on COPD was evaluated by the logistic regression model after propensity score matching (PSM). Finally, the participants were randomly divided into training and validation sets. The training set was used to screen the relative factors and construct a nomogram which was further assessed by the receiver operating characteristic (ROC) curve, calibration curve, and decision curve analysis (DCA) in the two sets. Results There were 2,486 eligible participants in the final analysis, of which 1,584 lived in low altitudes and 902 lived in high altitudes. Based on the GOLD criterion, the crude and standardized prevalences in Gansu were 20.4% (18.7–22.0) and 19.7% (17.9–21.6). After PSM, the logistic regression model indicated that high altitude increased COPD risk [PSM OR: 1.516 (1.162–1.978)]. Altitude, age, sex, history of tuberculosis, coal as fuel, and smoking status were reserved for developing a nomogram that demonstrated excellent discrimination, calibration, and clinical benefit in the two sets. Conclusions COPD has become a serious public health problem in Gansu. High altitude is a risk factor for COPD. The nomogram has satisfactory efficiency in screening high-risk individuals.